2022
DOI: 10.1021/acs.cgd.2c00046
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Covalent Organic Frameworks Based on Mixed Metallo- and Tetrahydroporphyrin Monomers for Use as Efficient Photocatalysts in Dye Pollutant Removal

Abstract: Unique features, including a high specific surface area, great stability, and crystallinity, make covalent organic frameworks (COFs) intriguing sorbents and catalysts in light-driven water pollutant degradation. Inspired by the light absorption capability of porphyrin derivatives and the carrier separation ability of a donor−acceptor (D−A) configuration, we constructed two-dimensional porphyrin donor-based D−A COFs: COF-HTBD involving only tetrahydroporphyrins and COF-HMTBD (M = Co, Fe, Cu) involving both tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…Accordingly, CF factors of various photocatalysts were compared with the reported literatures. The CF value of dDAAQ-TFP is 10.28, which is 26582, 243, 10 and 10 times greater than the COF-HTBB, 7 MWCNT, 3 Tp-Mela, 2 and CN600, 5 respectively. Most recently, Tp-Mela COF has been shown to be a highly effective metal-free carbonaceous photocatalyst for Fenton-like photodegradation.…”
Section: Impact Of Light Towards Photocatalytic Reactionsmentioning
confidence: 84%
See 1 more Smart Citation
“…Accordingly, CF factors of various photocatalysts were compared with the reported literatures. The CF value of dDAAQ-TFP is 10.28, which is 26582, 243, 10 and 10 times greater than the COF-HTBB, 7 MWCNT, 3 Tp-Mela, 2 and CN600, 5 respectively. Most recently, Tp-Mela COF has been shown to be a highly effective metal-free carbonaceous photocatalyst for Fenton-like photodegradation.…”
Section: Impact Of Light Towards Photocatalytic Reactionsmentioning
confidence: 84%
“…For instance, multiwalled carbon nanotubes (MWCNT), 3 reduced graphene oxide, 4 graphitic carbon nitride, 5 and photoelectron-Fenton like cell, 6 and COF-THTBD. 7 Among them, triazine linked Tp-Mela COF is reported as highly active photo Fenton-like activities over several colored and colorless pollutants. The efficiency of the Tp-Mela COF photocatalyst is much higher even than several metal-based photo Fenton-like systems.…”
Section: Introductionmentioning
confidence: 99%
“…[32] Compared with other photosensitive materials, COFs have better photocatalytic activity due to the extended π-conjugated frameworks, excellent crystallinity, and ordered pore structures. [33] In the past few decades, COFs containing porphyrins and their metal derivatives, [34][35][36][37] benzothiadiazole [38][39][40] or triazine [41][42][43] involve excellent photoelectric properties and demonstrate great potential in the fields of photocatalysis. On the basis of the excellent photoelectric property of COFs, it can be predicted that COFs also have unique nanozymatic activities and demonstrate great potential in the field of nanozymes.…”
Section: Introductionmentioning
confidence: 99%
“…Developing facile and cost-effective intermolecular modulating strategies to improve the dissociation of excitons and enhance the charge transfer in COFs thus is in great demand. , Via the electronic push–pull effect between donor and acceptor units, the donor–acceptor (D–A) structure constructed within COFs has been demonstrated to be one of the most promising intermolecular modulating strategies to decrease the exciton binding energy ( E b ) and facilitate charge transfer. For example, Liu et al found that porphyrin-based D–A COF (COF-HFeTBD) could facilitate charge separation and transfer, improving the photodegradation performance of rhodamine B. Yang et al also showed that conjugated D–A COF (TAPP-BDP) without any postsynthesis modification exhibited high antibacterial efficiency due to the efficient charge separation efficiency. Very recently, we fabricated a thiadiazole-based D–A COF (COF-TD1) with a rapid intramolecular charge transfer process (IRCT), which exhibited efficient photocatalytic degradation performance toward emerging contaminants .…”
Section: Introductionmentioning
confidence: 99%